PENGARUH MOTIVASI KERJA, INSENTIF DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN ALFAMART DI BLITAR - Erma Yusida; Eka Askafi; Imam Baehaki (FKDP (Forum Komunikasi Dosen Peneliti), 2021)
This study aims to examine the effect of work motivation, incentives and work environment on the performance of Alfamart employees in Blitar. The sample in this study were all employees of Alfamart Bakung Udanawu and Alfamart Tanjungsari Blitar, totaling 30 respondents. By using inferential statistical analysis methods. The results of data analysis and hypothesis testing show that work motivation, incentives and work environment have a significant effect on employee performance at Alfamart in Blitar. The results of the research prove that work motivation, incentives and work environment can improve employee performance at Alfamart.